IEEE Std 524a-1993 : IEEE Guide to Grounding During the Installation of Overhead Transmission Line Conductors (IEEE, 1994)
General recommendations for the selection of methods and equipment found to be effective and practical for grounding during the stringing of overhead trasmission line conductors and overhead ground wires are provided. The guide is directed to transmission voltages only. The aim is to present in one document sufficient details of present day grounding practices and equipment used in effective grounding and to provide electrical theory and considerations necessary to safeguard personnel during the stringing operations of transmission lines.